Coyuntura Económica - Martínez Sandoval, Avelino; Rozo, María Carolina; Aponte Bello, Guillermo; Sánchez Rengifo, Holmes; Vázquez Olave, Martha; Ángel Giraldo, Leidy (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2008)
Coyuntura Económica